(untitled) (Comprehensive Journal of Science, 2025)
As a result of the complete transformation of the Libyan banking system to work in accordance with the provisions of Islamic Sharia, rights and obligations resulted on banks for the period before the transformation process, which requires legal and economic treatments, as the Central Bank of Libya reports that the rate of profitability of banks in Libya has decreased as a result of the application of the law on the abolition of usurious interest, as the rate of return on assets in the banking sector in Libya witnessed a significant decline during the years (2014-2016). This study aims to identify and discuss the illegal financial obligations and rights that resulted from the transformation of the Libyan banking sector towards Islamic banking, and how to address them Shariah, through the perceptions of a group of experts and specialists in Sharia and finance on ways to address these rights and obligations and mitigate their potential negative effects on the financial performance of Libyan banks. The study found that the most important thing Libya needs now is a wise decision by the Central Bank of Libya to rearrange the transition by issuing appropriate laws that support the transition.